Pengaruh Keselamatan dan Kesehatan Kerja Terhadap Kinerja Karyawan PT. Citra Bina Maju Jaya Tangerang - martaatmadja, ayi krisnha w.a.n; roudotuljanah; nurazis (Universitas Tangerang Raya, 2022)
The purpose of this study is to know how occupational safety and health affect employees' performance both partial and simultaneous on PT. Citra Bina Maju Jaya Tangerang.A method of research used with quantitative research. The population in this study is all employees PT. Citra Bina Maju Jaya Tangerang. The sample used in this study was 80 respondents. The results of a statistical analysis of the data prove that variables of safety and work have a positive and significant impact on workers' performance simultaneously shown by the significant value of 0,000 < 0.05. Meaning no, it suggests